The effects of the adoption of blockchain technology on selected ASEAN banks’ stock performance: An event study - Lopez, Angelo Gabriel G. (Animo Repository, 2022)
The study aims to determine the impact of the announcement of blockchain technology use on select ASEAN banks stock price. As the financial technology industry takes its innovative step forward decentralizing many traditional financial services, public sentiment has yet to be decided on how this will affect the existing industries moving forward. This study takes into account the efficient market hypothesis and its forms as well as how it applies to the ASEAN markets. Market efficiency levels differ from country to country and the study seeks to discover how far the limits of the announcement effect can contribute to volatility of stock prices and whether or not blockchain technology is seen by market sentiment as a significant provider of value to shareholders. Tying together the degree of market efficiency, the announcement effect, and its connection to the implementation of blockchain technology, the research sample is limited only to the ASEAN region and the finite amount of publicly traded banks which have adopted blockchain technology.